2012
DOI: 10.5070/p23s31
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Citizen Support for Direct Democracy

Abstract: Direct democracy is extraordinarily popular and has become a pervasive policymaking tool at the state and local level. Repeated surveys demonstrate that Americans strongly approve of allowing people to vote on citizen-proposed laws, a method currently allowed in about half the states and in many municipalities. This paper examines the extent of this support. Using dimension reduction techniques, we present evidence that demonstrates that with regards to approval of direct democracy, most voters find themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moreover, much research has emphasized polls showing that the process remains generally popular with the public. However, recent analysis has called into question the depth of such support, and suggested that citizens -including Californians -are in fact quite supportive of some reforms (see especially Dyck and Baldassare 2012). For example, a 2006 survey by the Center for Governmental Studies (2008) found that although 45% of respondents were somewhat satisfied and 37% of respondents not satisfied with the initiative process at all, 80% of the respondents believed in the idea of the initiative process and the ability of voters to make decisions on proposed laws (Center for Governmental Studies 2008, p. 348).…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Moreover, much research has emphasized polls showing that the process remains generally popular with the public. However, recent analysis has called into question the depth of such support, and suggested that citizens -including Californians -are in fact quite supportive of some reforms (see especially Dyck and Baldassare 2012). For example, a 2006 survey by the Center for Governmental Studies (2008) found that although 45% of respondents were somewhat satisfied and 37% of respondents not satisfied with the initiative process at all, 80% of the respondents believed in the idea of the initiative process and the ability of voters to make decisions on proposed laws (Center for Governmental Studies 2008, p. 348).…”
Section: Summary and Implicationsmentioning
confidence: 99%